Tribological performance of PTFE-ATSP and PTFE-Ekonol polymer blends aimed for oil-less engineering applications (2023)
This study examines the tribological performance of an advanced high-performance polymer (HPP), namely aromatic thermosetting copolyester (ATSP), and poly-hydroxybenzoic acid polymer or Ekonol® as additives for polytetrafluoroethylene (PTFE), under unlubricated conditions from room temperature to 300 ◦C. Compared to PTFE-Ekonol composites, PTFE-ATSP blends showed 50% reduction in the wear rate at all tested temperaturas and higher wear resistance at different sliding speeds, partially attributed to its viscoelastic stability or higher mechanical strength. Also, a fluoride-rich lubricating transfer film was formed on the metallic counter Surface when tested against PTFE-ATSP, and this film is temperature-dependent. PTFE-ATSP blends are an attractive solution for oil-less applications in the temperature range of 25–300 ◦C.